Pre-trial protocol in civil proceedings - Bekturganov, M.Zh.; Maxatov, N.R.; Moroz, S.P. (Bulletin of the Karaganda University “Law Series”, 2024)
The scientific article examines the legal nature of the pre-trial protocol in civil proceedings. The institution of judicial evidence was subject to change in connection with the latest reforms of the civil procedure legisla-tion. This has led to the emergence of new institutions and the pre-trial protocol in civil proceedings is such. Until 2022, the Civil Procedure Code of the Republic of Kazakhstan (hereinafter CPC RK) did not have di-rect legal regulation of this institution, and accordingly, no theoretical studies were conducted on this issue. In civil proceedings, the prototype of the institute of pre-trial protocol was a foreign legal institution, such as the disclosure of evidence and the exchange of arguments, characteristic of English and American procedural law. The practical necessity of many aspects of such a phenomenon as the pre-trial protocol, the incomplete-ness of theoretical developments and the need to improve legislation determined the relevance of the topic of the scientific article. It should be recognized that the mechanism for drawing up a pre-trial protocol, in fact, designed to ensure the implementation of the principles of competition and equality of the parties, was not sufficiently enshrined in the civil procedural legislation of the Republic of Kazakhstan. At the same time, consistent legislative regulation of the activities of bodies for the disclosure of evidence in civil proceedings is required. The institution of pre-trial protocol in civil proceedings requires regulation and integration at the legislative level, since the mechanism of conclusion in the current CPC of the Republic of Kazakhstan has not been fully investigated.